The Relationship between Student Engagement and School Well-Being - Rudy Yuniawati; Ismiradewi Ismiradewi (Universitas Ahmad Dahlan, 2018)
The purpose of the present study was to examine the relationship between student engagement and school well-being. This study employed quantitative approach with correlational design. The subject of the study was 265 students who were selected by using cluster random sampling technique. The data were collected by using student engagement scale and school well-being scale. The data were analyzed using product moment. The result of the analysis obtained R of 0.790 with significance level of 0.000 (p <0.01). The result of the study showed that the level of school well-being is strongly affected by student engagement. The result of the study provides contribution to the development of guidance and counseling concerning student engagement and school well being.